2016
DOI: 10.4251/wjgo.v8.i7.526
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic injury in patients with septic shock: A literature review

Abstract: Sepsis and septic shock are life threatening condition associated with high mortality rate in critically-ill patients. This high mortality is mainly related to the inadequacy between oxygen delivery and cellular demand leading to the onset of multiorgan dysfunction. Whether this multiorgan failure affect the pancreas is not fully investigated. In fact, pancreatic injury may occur because of ischemia, overwhelming inflammatory response, oxidative stress, cellular apoptosis and/or metabolic derangement. Increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 64 publications
0
27
0
3
Order By: Relevance
“…Possible reasons for this conclusion extrapolated from human medicine include inflammation secondary to the underlying disorder causing renal injury, multiorgan failure, and ischemia or hypoperfusion because of changes in plasma volume. 4,9,39 Other primary nonpancreatic disorders frequently associated with significantly increased DGGR-lipase activities in our study were endocrinopathies, immune-mediated disorders, and upper airway obstruction. Diabetes mellitus and AP are common comorbidities; a previous study found diabetes mellitus in 36% of dogs diagnosed with AP, 40 and another identified cPL concentrations >400 μg/L in 73% of dogs with DKA.…”
Section: Discussionmentioning
confidence: 58%
“…Possible reasons for this conclusion extrapolated from human medicine include inflammation secondary to the underlying disorder causing renal injury, multiorgan failure, and ischemia or hypoperfusion because of changes in plasma volume. 4,9,39 Other primary nonpancreatic disorders frequently associated with significantly increased DGGR-lipase activities in our study were endocrinopathies, immune-mediated disorders, and upper airway obstruction. Diabetes mellitus and AP are common comorbidities; a previous study found diabetes mellitus in 36% of dogs diagnosed with AP, 40 and another identified cPL concentrations >400 μg/L in 73% of dogs with DKA.…”
Section: Discussionmentioning
confidence: 58%
“…Sepsis and septic shock is an extremely life threatening, and can lead to high mortality rates in critically-ill patients. It is mostly associated with insufficiency between demand of cells and the delivery of oxygen, which caused the beginning of multi-organ dysfunction [ 1 ]. Sepsis is characterized by an overwhelming host response and development of remote organ failure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the involvement of these factors in the physiopathology of pancreatic insult may explain the occurrence of this complication in patients without significant hemodynamic compromise [6, 17]. Our study also showed that the impairment of renal function was significantly associated with sepsis-related increase of pancreatic enzymes.…”
Section: Discussionmentioning
confidence: 51%
“…The APACHE (II) score calculated within the first 24 h was 26 [20–31]. Median SOFA score on admission was 7 [610]. Thirty patients (60%) were diabetic, and 32 patients (64%) have previous history of hypertension.…”
Section: Resultsmentioning
confidence: 99%